Accuracy of hydrocortisone dose administration via nasogastric tube. (9th November 2018) - Daniel, Eleni; Whitaker, Martin J.; Keevil, Brian; Wales, Jerry; Ross, Richard J.
Summary: Objective: Hydrocortisone via nasogastric (NG) tube is used in sick children with adrenal insufficiency; however, there is no licensed formulation for NG administration. Methods: We investigated hydrocortisone recovery after passage through NG tubes in vitro for three formulations: liquid suspension, crushed tablets mixed with water, and hydrocortisone granules designed for oral administration to children. Cortisol was measured by LC‐MS/MS. Results: Hydrocortisone content was variable and recovery low after preparation in syringe and prior to passage through NG tubes. For doses, 0.5 and 2.0 mg mean percentage recovery was as follows: liquid suspension 57% and 58%; crushed tablets 46% and 30%; and hydrocortisone granules 78% and 71%. Flushing the administering syringe increased recovery. Hydrocortisone recovery after passage with flushing through 6‐12Fr gauge NG tubes was variable: liquid suspension 61%‐92%, crushed tablets 40%‐174%, hydrocortisone granules 61%‐92%. Administration of hydrocortisone granules occluded 6 and 8Fr NG tubes; however, administration using a sampling needle to prevent granules being administered gave a recovery of 74%‐98%. Conclusions: The administration of hydrocortisone through NG tubes is possible; however, current methods deliver a variable dose of hydrocortisone, generally less than that prescribed. Attention should be placed on the technique used to optimize drug delivery such as flushing of the administering syringe. Hydrocortisone granules block small NG tubes but behaved as well as the commonly used liquid suspension when prepared with a filtering needle that filters out granules.